Comparative Analysis of Customer Acceptance of Digital Wallet Gopay, Dana and Ovo Using Unified Theory of Acceptance and Use of Technology - Sudirjo, Frans; Ahmad Yani, David; Suroso, Amat; Kadarsih; Ar Rakhman Awaludin, Aulia (SEULANGA SYSTEM PUBLISHER, 2023)
Finding out what variables affect users' acceptance of server-based electronic wallets is the goal of this study. A quantitative methodology is used in this investigation. Using a questionnaire, a survey was conducted in order to collect data. Users of server-based electronic wallets make up the study's population. The purposive sampling strategy was employed by the author in this study. It was successful for the author to get 100 responses. Statistical analysis and demographic analysis are the two subcategories of data analysis. Using IBM SPSS, the author first analyzed demographic data. Second, SmartPLS was used by the author to perform statistical analysis. The following are the factors that affect user approval, according to the research findings: The impact of effort depletion on behavioral intention is substantial. An important factor influencing behavioral intention is social influence. The impact of perceived trust anticipation on behavioral intention is substantial. Behavior intention is significantly impacted by perceived risk anticipation. Encouraging circumstances behavioral intention is significantly influenced by expectations. Use behavior is significantly impacted by facilitating situations. Behavioral intention is significantly impacted by habit. The way we utilize things is greatly influenced by our habits. The intention behind one's behavior greatly influences how they use things. In the meanwhile, performance expectation has no discernible impact on behavioral intention, and the following criteria do not influence user approval. There is no discernible impact of hedonic motivation on behavioral intention. On behavioral intention, price value has no discernible impact.